Simulation of Deformation Process Failure of Jointed Rock Masses Based on the Numerical Manifold Method - Lin, Xing-Chao; Zhang, Qiang; Jin, Jiufeng; Chen, Guangming; Li, Jin-Hang (Frontiers in Physics, 2022)
On the basis of the numerical manifold method, this work introduces the concept of stress intensity factor at the crack tip in fracture mechanics and proposes the utilisation of artificial joint technology to ensure the accuracy of joint geometric dimensions in the element generation of the numerical manifold method. The contour integral method is used to solve the stress intensity factor at the joint tip, and the failure criterion and direction of crack propagation at the joint tip are determined. Element reconstruction and crack tracking are implemented in crack propagation, and a simulation programme of the entire process of deformation, failure, propagation and coalescence of jointed rock masses is developed. The rationality of the proposed method is verified by performing the typical uniaxial compression test and direct shear test.